Development of multiple intelligence test instrument for teen students in perspective of physics learning. Issue 3 (February 2019) - Kurniawan, A; Rustaman, N Y; Kaniawati, I; Hasanah, L
Abstract: The purpose of this study is to develop multiple intelligence instruments for teen students (15-19 years old). The research method used mixed-method with asequential explanatory design. The research activities were conducted in the odd semester of the academic year 2017/2018. The subjects of the study were the students of class X and XI in one of the private vocational school in Bandung consisting of one class for each random sampling. The results showed that the multiple intelligence test instrument developed in this study has been able to provide a profile picture of multiple intelligences owned by middle-agedstudents. This multiple intelligence profiles can be used as a basis that can be used by teachers in the design of physics learning in the classroom. The profiles of multiple intelligences result obtained: musical intelligence 9 students, kinesthetic intelligence 8 students, logical mathematic intelligence 8 students, spatial intelligence 3 students, 7 linguistic intelligence 7 students, interpersonal intelligence 7 students, intrapersonal intelligence 8 students, and naturalist intelligence 7 students.